2004
DOI: 10.1501/sporm_0000000027
|View full text |Cite
|
Sign up to set email alerts
|

Beden eğitimi öğretmenleri ile diğer branş öğretmenlerinin problem çözme becerisi açısından karşılaştırılması

Abstract: ÖZETBu araştırmanın genel amacı; beden eğitimi öğretmenleri ile diğer branş öğretmenlerinin problem çözme becerisindeki algılama düzeyleri arasındaki farkı analiz etmektir. Araştırmanın örneklem grubunu; 194 beden eğitimi öğretmeni ile 118 diğer branş öğretmeni (sosyal bilgiler, fen bilgisi, felsefe ve yabancı dil grubu) olmak üzere toplam 312 öğretmen oluşturmaktadır. Veriler, 1982 yılında P.P Heppner ve C. H. Petersen tarafından geliştirilen ve özgün adı "Problem Solving Inventory, Form-A (PSI-A) olarak adla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
1
2
0
1
Order By: Relevance
“…Although there was no statistically significant difference between the total scores of the multi-dimensional 21 st Century Skills Scale of female and male gifted students, the Critical Thinking and Problem Solving Skills subscale scores of the scale are in favor of the female participants statistically significant difference was found. This result is similar to some studies conducted with different student groups (Arlı, Altunkaya and Yalçınkaya, 2011;Bozkurt and Çakır, 2016;Demirtaş and Dönmez, 2008); it differs with some studies (Kölemen and Erişen, 2017;Pehlivan and Konukman, 2004). For example, Kölemen and Erişen (2017) concluded that the gender of the students was not related to these skills.In addition, a significant difference was found in favor of female participants between the scores obtained from the sub-dimensions of Entrepreneurship and Innovation Skills and Career Awareness Skills of the average students.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although there was no statistically significant difference between the total scores of the multi-dimensional 21 st Century Skills Scale of female and male gifted students, the Critical Thinking and Problem Solving Skills subscale scores of the scale are in favor of the female participants statistically significant difference was found. This result is similar to some studies conducted with different student groups (Arlı, Altunkaya and Yalçınkaya, 2011;Bozkurt and Çakır, 2016;Demirtaş and Dönmez, 2008); it differs with some studies (Kölemen and Erişen, 2017;Pehlivan and Konukman, 2004). For example, Kölemen and Erişen (2017) concluded that the gender of the students was not related to these skills.In addition, a significant difference was found in favor of female participants between the scores obtained from the sub-dimensions of Entrepreneurship and Innovation Skills and Career Awareness Skills of the average students.…”
Section: Discussionsupporting
confidence: 88%
“…Yüzyıl Becerileri Ölçeği'nden aldıkları ortalama puanlar arasında istatistiki olarak anlamlı düzeyde bir farklılık olmamasına karşın, ölçekte yer alan Eleştirel Düşünme ve Sorun Çözme Becerileri alt boyutundan kadın ve erkek katılımcıların elde ettikleri puanlar arasında kadın katılımcılar lehine anlamlı düzeyde bir farklılığın olduğu belirlenmiştir. Elde edilen bu sonuç, farklı öğrenci grupları ile yürütülen bazı çalışmalarla benzerlik (Arlı, Altunay ve Yalçınkaya, 2011;Bozkurt ve Çakır, 2016;Demirtaş ve Dönmez, 2008); bazı çalışmalarla farklılık göstermektedir (Kölemen ve Erişen, 2017;Pehlivan ve Konukman, 2004). Örneğin Kölemen ve Erişen (2017), bireylerin cinsiyetleri ile ifade edilen beceriler arasında bir ilişkinin olmadığını belirtmişlerdir.…”
Section: öZel Yetenekli öğRencilerin öLçekteki Eleştirel Düşünme Ve Sorun çöZmeunclassified
“…As a result of the research conducted by Civan et al (2010) with individual and team athletes, there was no significant difference in terms of trait anxiety scores in terms of gender status (Civan et al, 2010). Determined that the problem solving skills of physical education teachers did not change according to the duration of service in the profession (Pehlivan and Konukman, 2004). Kutanis and Tuna (2013), in their study with nurses, did not reveal a significant relationship between working time in the profession and their anxiety scores (Kutanis and Tuna, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…It is known that people who are engaged in sports have various personality features such as being free, objective, and very little anxious than those who do not. It is also undeniable that individuals who do sports face too many issues (Pehlivan and Konukman, 2004).…”
Section: Discussionmentioning
confidence: 99%